Družinski centri v različnih sistemih blaginje - Rakar, Tatjana (Socialno delo, 2012)
Family centres as a form of family help programmes are an important measure of the welfare state in the promotion of family friendly environment for the reconciliation of work and family life and for equal opportunities policies. Existing welfare systems, such as the conservative-corporatist, social-democratic, liberal, catholic and former state-socialist types are based on different hierarchies of spheres (such as the market, state, civil society and community) from which we obtain resources for social protection and welfare. The consequences of these differences in the hierarchies are the different levels of decommodification and defamiliarisation in society. As a consequence, the role of family centres also differs among different welfare systems. On the basis of comparative analysis of the characteristics of family centres in chosen countries the article shows that the welfare system and its defamiliarisation level have an important influence on the development and the role of family centres.
Keywords: Family; družina; družinska politika; Family policy; sistemi blaginje; Welfare state; družinski centri